High cereblon expression in neuroendocrine cancer confers vulnerability to GSPT1 molecular glue degrader - Jaewoo Park; Min Sung Joo; Myung Jun Kim; Seungseok Oh; Phuong Thao Tran; Minju Kwon; Yong June Choi; JaeYung Lee; Eun-Jung Kim; Dong Hyuk Ki; Hunmi Choi; Wooseok Han; et al. (Experimental Hematology & Oncology, 2025)
Abstract Background Recent advances in targeted therapies have introduced molecular glue degraders (MGDs) that leverage the cereblon (CRBN) E3 ubiquitin ligase to degrade the translation termination factor GSPT1. Understanding the cellular context for the selective targeting of cancer cells by GSPT1 MGDs is crucial. Methods This study investigated the sensitivity of neuroendocrine cancer (NEC) cells to GSPT1MGDs across a pan-cancer cell line panel, examining the correlation between therapeutic response and cellular characteristics such as CRBN expression and neuroendocrine (NE) marker levels. The role of CRBN in enhancing MGD sensitivity was further validated through CRBN overexpression and NEC-driving factor expression experiments in non-NEC and lung adenocarcinoma cells. The sensitivity of acute myeloid leukemia (AML) cells, which share transcriptomic features with NECs, to GSPT1 MGDs was also evaluated. Results NEC cells with high CRBN expression exhibited marked sensitivity to GSPT1 MGDs compared to other cancer types. GSPT1 degradation was more rapid and robust in NEC cells, highlighting the cellular context dependency of the treatment. A strong correlation was observed between CRBN expression and NE characteristics, whereas no such correlation was found with GSPT1 expression. CRBN overexpression in non-NEC cells significantly increased their sensitivity to GSPT1 MGDs, as did the ectopic expression of NEC-driving factors, which upregulated CRBN levels in lung adenocarcinoma cells. Additionally, AML cells, with high CRBN expression, showed similar sensitivity to GSPT1 MGDs, mirroring the behavior of NECs. Conclusions CRBN expression is a critical determinant of the selective cytotoxicity of GSPT1 MGDs in NECs and other cancers with shared transcriptomic features, such as AML. These findings underscore the therapeutic potential of targeting NECs using GSPT1 MGDs, paving the way for a more refined and selective approach in treating aggressive cancers.